2004
DOI: 10.3748/wjg.v10.i11.1647
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of gastroesophageal reflux disease: A general population-based study in Xi’an of Northwest China

Abstract: GERD is common in Xi'an's adult population with a mild or moderate degree. The etiology and pathogenesis of GERD are probably associated with FD, IBS, and some respiratory, laryngopharyngeal and odontostological diseases or symptoms. Some lifestyles, diseases and dietary factors are the risk factors of GERD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
139
4
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(169 citation statements)
references
References 39 publications
17
139
4
9
Order By: Relevance
“…Epidemiological studies that examined the relationship between coffee and GERD Of the 15 epidemiological studies, only 5 studies concluded that GERD symptoms were associated with coffee intake (Table 1) (Bhatia et al, 2011;Lee et al, 2011;Somi et al, 2006;Wang et al, 2004;Castelo Vega et al, 2003). These included an Indian prospective,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological studies that examined the relationship between coffee and GERD Of the 15 epidemiological studies, only 5 studies concluded that GERD symptoms were associated with coffee intake (Table 1) (Bhatia et al, 2011;Lee et al, 2011;Somi et al, 2006;Wang et al, 2004;Castelo Vega et al, 2003). These included an Indian prospective,…”
Section: Resultsmentioning
confidence: 99%
“…Another cross-sectional study (Somi et al, 2006) also found drinking coffee was associated with higher prevalence of GERD symptoms. Wang et al (2004) and Castelo Vega et al (2003) found consumption of coffee was independently associated with symptomatic gastroesophageal reflux (OR = 1.23; CI: 0.17 − 2.00 & OR = 4.39; CI: 1.72 − 11.65).…”
Section: Sources Of Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors 8,21,[26][27][28] have demonstrated an association between alcohol consumption and gastro-esophageal reflux disease. Our study too has shown that there was a significant association between prolonged consumption of alcohol and gastro-esophageal reflux disease.…”
Section: Gerd and Psychological Co-morbiditymentioning
confidence: 99%
“…The alcohol consumption was (294.2±73.4) g/week in the symptomatic group and (53.2±13.4) g/week in the asymptomatic group (Nozu and Komiyama, 2008). Chronic excessive alcohol abuse has also been shown to be associated with GERD (odds ratio (OR)=2.85, 95% confidence interval (CI): 1.67-4.49) (Wang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%